The Method of Modeling the Characteristics of a Swarm of UAVs as an Object with Distributed Parameters Based on the Analysis of Interval Data - Dyvak, Mykola; Porplytsya, Natalia; Spivak, Iryna; Tymchyshyn, Vasyl; Krepych, Svitlana; Taraj, Martin (International Conference on Advanced Computer Information Technologies (Print), 2023)
-A number of scientific studies using UAV swarms are considered. The expediency of developing mathematical models of UAV swarm characteristics as an object with distributed parameters for problems of interval data analysis is shown. A computational scheme for building model of the distribution of harmful emissions of vehicle exhaust gases is proposed. The verification of the built model was carried out on test data obtained for the specified observation area, which confirmed the sufficient prognostic properties of the model.